2015
DOI: 10.4236/oalib.1101549
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Chromium Doped Zinc Sulfide Nanoparticles

Abstract: Nanoparticles of pure and Zn 1−x Cr x S with concentrations (x = 0.00, 0.02, 0.08 and 0.10) were prepared successfully by co-precipitation technique. Crystallographic study was intervened by X-ray diffraction spectroscopy. There were no extra peaks observed in the XRD pattern. From XRD peaks it is confirmed that the samples prepared were highly pure and cubic in structure. The particle size calculated from XRD data was around 3 nm. It confirms that the quantum dots were formed. Surface morphology and crystal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…With the Fourier transform infrared (FTIR) analysis, the absorbance of the species in the crystal surface and the nanoparticle formation of ZnS were checked. It is reported that this analysis also gives information about the chemical bonding of the chemical [ 17 ]. The FTIR absorbance spectra of Cr x ZnS with different molar ratios are shown in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…With the Fourier transform infrared (FTIR) analysis, the absorbance of the species in the crystal surface and the nanoparticle formation of ZnS were checked. It is reported that this analysis also gives information about the chemical bonding of the chemical [ 17 ]. The FTIR absorbance spectra of Cr x ZnS with different molar ratios are shown in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…21(a) illustrates the cubic structure of the nanoparticles, which is further supported by XRD. 96 Using the chemical co-precipitation method, Ahmed, AL-Osta, et al created Cr-added ZnS nanoparticles, and ultravioletvisible spectra confirmed that with the increment in the doping Fig. 18 PL spectra of lead-doped ZnS nanoparticles.…”
Section: Chromium (Cr)-doped Znsmentioning
confidence: 99%
“…21 (a) X-ray diffraction patterns of undoped and Cr-doped ZnS nanoparticles. 96 (b) Optical energy gap vs Cr doping amount, 97 and (c) Cr-doped ZnS PL spectra at various annealing temperatures. 98 increased with increased Fe doping.…”
Section: Iron (Fe)-doped Znsmentioning
confidence: 99%
“…In addition, it affects the structural and optical properties and can considerably shi the optical absorption towards the visible region. [17][18][19][20] However, electrical conductivity in the wide band gap of ZnO semiconductors is due to intrinsic defects such as wide band gap and oxygen vacancies. Therefore, substitution of TM metals into ZnO semiconductors changes structural and optical properties drastically.…”
Section: Introductionmentioning
confidence: 99%